Peningkatan kemampuan komunikasi matematis dan self regulated learning siswa melalui model problem based learning (pbl) - Intan Fauziah; Samsul Maarif; Trisna Roy Pradipta (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2018)
Penelitian ini bertujuan untuk menyelidiki perbedaan peningkatan kemampuan komunikasi matematis yang diajarkan dengan model PBL dan yang diajarkan dengan pendekatan scientific; menyelidiki keterkaitan antara self regulated learning dan kemampuan komunikasi matematis siswa. Populasi penelitian ini adalah seluruh siswa kelas VII yang ada di SMP Negeri 205 Jakarta. Teknik pengambilan sampel menggunakan cluster random sampling. Metode penelitian yang digunakan adalah Quasi Eksperimen dengan desain pretest-posttest control group design. Sampel yang digunakan sebanyak 36 siswa dari kelas eksperimen dan 36 siswa dari kelas kontrol. Hasil penelitian ini mengungkapkan bahwa terdapat perbedaan peningkatan kemampuan komunikasi matematis antara siswa yang diajarkan dengan model PBL dan siswa yang diajarkan dengan pendekatan scientific; terdapat keterkaitan (hubungan) antara self regulated learning dan kemampuan komunikasi matematis siswa.Improvement of mathematical communication skills and self-regulated learning through problem based learning (PBL) modelsThe purpose of this research to investigate differences of the increasing mathematics communication ability which used to problem based learning model, investigate correlation between self-regulated learning and mathematics communication ability. Method of this research used to quasi experiment with pretest-posttest control group design. The population of this study is 7th grader students of 205 Junior High School in Jakarta, then This research used 36 students from control class and 36 students from experiment class. The determination of sample used cluster random sampling. The result of this research are, there is a difference improvement of students mathematics communication ability which thought used to PBL models and scientific, there is correlation between students self-regulated learning and mathematics communication ability.